Large Epidermoid Cyst in Submental Region: A Rare Case Report - Sadat, S M Anwar; Chowdhury, Taslima Akter; Rahman, Asadur; Rita, Sufia Nasrin (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Epidermoid cyst, specially in large size is one of the rare lesions of maxillofacial region, affects submental and sublingual region. The cyst develops from the entrapment of pluripotent ectodermal and mesodermal primordia, in the embryonic lines of fusion, when first and second branchial arches of each fuse in the midline, between third and fourth weeks of intrauterine life. After entrapment, this tissue shows gradual proliferation and ultimately transform to a cyst. A 19-year-old-boy presented with such a midline painless large swelling in the submental and sublingual region with diagnosis of epi dermoid cyst. After enucleation, the patient didn’t show any recurrence after 2 years follow up. J Bangladesh Coll Phys Surg 2024; 42: 92-96